COMPUTER ALGORITHM FOR DETERMINATION OF MATERIAL FLOW RELATIONS - Telek, Péter (Advanced Logistic Systems - Theory and Practice, 2016)
First step of the design of a materials handling process is the analysis of the required material flow to determine the base parameters, which depend on the materials handling relations of the system objects. Materials handling relation means a special connection between two objects, which contains any kind of handling activity. The problem with the relations is the determination procedure, because there are no direct transformation possibility between the technology and handling parameters. In this paper a computer algorithm is described, which is suitable to determine the handling relations and matrices of an existing materials handling system, based on technology data and to demonstrate the process, and beyond them one solution possibility for the realisation of the computer method for the calculation procedure is also presented.